Migración haitiana en Chile 2020: barreras a la incorporación social, arraigo cuestionado y re-emigraciones (2021)
The following is an anthropological approach, in a context of health state of emergency, institutional crisis and citizenship crisis in Chile. It refers to a young population of Haitian residents, with difficulties to exercise the right to the city within the principles of democracy, equality and social justice, for which they are subject to alterity in a subaltern way, due to daily and institutional racism. We review some of the actions taken by Chilean authorities in 2020, within the framework of the pandemic, to analyze how they affect them from the perspective of their citizenship rights, by focusing on economic informality, work and access to housing, situations that have effects on the evaluation of the migratory project and its intentions to settle, increasing their departure from Chile.